The eccentric:concentric strength ratio of human skeletal muscle in vivo: meta-analysis of the influences of sex, age, joint action, and velocity - Nuzzo, J. L.; Pinto, M. D.; Nosaka, K.; Steele, J. (Sports Medicine, 2023)
For decades, researchers have observed that eccentric (ECC) muscle strength is greater than concentric (CON) muscle strength. However, knowledge of the ECC:CON strength ratio is incomplete and might inform resistance exercise prescriptions. Our purposes were to determine the magnitude of the ECC:CON ratio of human skeletal muscle in vivo and explore if sex, age, joint actions/exercises, and movement velocity impact it. A total of 340 studies were identified through searches. It was possible to analyse 1516 ECC:CON ratios, aggregated from 12,546 individuals who made up 564 groups in 335 of the identified studies. Approximately 98% of measurements occurred on isokinetic machines. Bayesian meta-analyses were performed using log-ratios as response variables then exponentiated back to raw ratios. The overall main model estimate for the ECC:CON ratio was 1.41 (95% credible interval [CI] 1.38-1.44). The ECC:CON ratio was slightly less in men (1.38 [CI 1.34-1.41]) than women (1.47 [CI 1.43-1.51]), and greater in older adults (1.62 [CI 1.57-1.68]) than younger adults (1.39 [CI 1.36-1.42]). The ratio was similar between grouped upper-body (1.42 [CI 1.38-1.46]) and lower-body joint actions/exercises (1.40 [CI 1.37-1.44]). However, heterogeneity in the ratio existed across joint actions/exercises, with point estimates ranging from 1.32 to 2.61. The ECC:CON ratio was most greatly impacted by movement velocity, with a 0.20% increase in the ratio for every 1°/s increase in velocity. The results show that ECC muscle strength is ~ 40% greater than CON muscle strength. However, the ECC:CON ratio is greatly affected by movement velocity and to lesser extents age and sex. Differences between joint actions/exercises likely exist, but more data are needed to provide more precise estimates.